High gene flow and limited population structure in chinstrap penguin (Pygoscelis antarcticus) populations - Mura-Jornet, Isidora
Historical and contemporary climate change has impacted Antarctic biota affecting species distribution, demography and connectivity. In Antarctic marine environments, seabirds are important bioindicators of ecological change and can respond to climate change in two main ways: local adaptation or dispersal. To characterise connectivity, sex-biased dispersal, diversity and genetic structure 12 microsatellite loci and a fragment of CHD1 gene on 12 breeding colonies in the South Shetland Islands and the West Antarctic Peninsula (WAP), and one previously unstudied sub-Antarctic island 3,600 km away from the WAP (Bouvetøya). High genetic diversity and evidence of female bias-dispersal were detected. Limited population genetic structure and lack of isolation by distance throughout the region were found, along with no differentiation between the WAP and Bouvetøya (overall microsatellite FST = 0.0016, p = 0.273), indicating large distance dispersal. Therefore, genetic assignment tests could not assign individuals to their population(s) of origin. The most differentiated location was Georges Point, one of the southernmost breeding colonies of this species in the WAP. The subtle differentiation found may be explained by some combination of low natal philopatric behaviour, high rates of dispersal and/or generally high mobility among colonies of chinstrap penguins compared to other Pygoscelis species.